(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This paper examines the interior architectural design of columbaria and its impact on spiritual development within contemporary Chinese society. In a secularized world where traditional cemeteries are often seen as unwelcoming, columbaria offer a modern alternative for the interment of the deceased. This study aims to explore how columbarium design can create a meaningful sense of place and fulfill spiritual needs, addressing a gap in research between sacred and secular with the design of the columbarium. Through literature reviews and a case study on Penang’s columbaria, the paper documents how elements of design approaches can determine if the space leans more into the sacred or the secular. The paper will conclude that by determining the factors of scared and secular design approaches, future design of columbarium can be more mindful in balancing a space to be both a sacred space to foster spiritual connection and a secular one to be more relatable with society, a secular space with sacred qualities.